Grodno – forgotten garrison of the second republic of Poland - Jędrzejewska, Agnieszka (City and War, 2021)
In the years 1921–1939 one of the largest military garrisons operated in Grodno. Its strength and importance was evidenced by the presence of regular troops as well as the authorities and military institutions that had their headquarters in this city. Many famous officers who actively participated in the life of the city were associated with the Grodno garrison. The history of the garrison is full of events such as daily service, matters of training and discipline, education and upbringing of soldiers. It is also a sport and the participation of garrison officers in various events that go beyond their daily duties. Its character and significance changed after the withdrawal of regular military units to fight the Germans, just before the outbreak of World War II. The garrison ceased to exist in September 1939 and did not revive after 1945. The aforementioned extensive subject exceeds the framework of the presented text, therefore only some of the threads are presented. They are only a small fragment of the garrison’s history, the history of which is not widely known. Despite the rich source base gathered in the Central Military Archives in Warsaw, in the National Historical Archives of Belarus in Grodno and information contained in the pre-war press, the Grodno garrison’s monograph has not yet been created.